CHRNA3 rs1051730 genotype and short-term smoking cessation. - Munafò, MR; Johnstone, E; Walther, D; Uhl, G; Murphy, M; Aveyard, P (2011)
INTRODUCTION: The rs1051730 genetic variant within the CHRNA5-A3-B4 gene cluster is associated with heaviness of smoking and has recently been reported to be associated with likelihood of stopping smoking. We investigated the potential association of rs1051730 genotype with reduced likelihood of smoking cessation in 2 cohorts of treatment-seeking smokers in primary care in the United Kingdom. METHODS: Data were drawn from 2 clinical trials on which DNA was available. One sample was a randomized placebo-controlled trial of nicotine transdermal patch and the other sample an open-label trial where all participants received nicotine transdermal patch. Smoking status was biochemically verified. Logistic regression was used to assess evidence for association in each sample, and data were combined within a meta-analysis. RESULTS: There was evidence of association of rs1051730 genotype with short-term (4-week) cessation in our open-label trial sample but not our placebo-controlled trial sample. When combined in a meta-analysis, this effect remained. There was no evidence of association at later follow-up intervals. Adjustment for cigarette consumption and tobacco dependence did not alter these results substantially. CONCLUSIONS: Our data, taken together with previous recent studies, provide some support for a weak association between this variant and short-term smoking cessation in treatment-seeking smokers, which does not seem to operate only among those receiving nicotine replacement therapy. Moreover, the rs1051730 variant may not merely operate as a marker for dependence or heaviness of smoking.